World Literature and the Fin-de-siècle in Latvian Literary Culture - Benedikts Kalnačs (Ars & Humanitas)
This article traces the main aspects of Shakespeare’s reception and interpretation in fin-de-siècle Latvian literary culture as a case study of the interaction of local literary culture with world literature. In the introduction, the principal factors instrumental for Shakespeare’s growing impact on European drama and theatre are scrutinized, paying special attention to eighteenth- and nineteenth-century German drama theories as well as theatrical practices. The article then proceeds by tracing the rise of vernacular theatres in East-Central Europe, focusing on Latvian theatre in the second half of the nineteenth century. In the final part, the article explores the potential affinities of the creative output of the Latvian dramatist Rūdolfs Blaumanis and William Shakespeare.